2017
DOI: 10.1097/mpa.0000000000000749
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for Pain in Chronic Pancreatitis

Abstract: The study presents proof-of-concept for the analgesic effect of acupuncture in pancreatic pain. Although the effect was short lasting, the framework may be used to conceptualize future trials of acupuncture in visceral pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…There were seven studies with human subjects. Two studies included irritable bowel syndrome (IBS) patients [15, 16], and one study involved primary dysmenorrhea [17] and another study involved chronic pancreatitis patients [18]. Further, a study by Kotani et al [19] investigated postoperative visceral pain in patients who underwent upper or lower abdominal surgeries [18], and two studies involved healthy participants [20, 21] (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There were seven studies with human subjects. Two studies included irritable bowel syndrome (IBS) patients [15, 16], and one study involved primary dysmenorrhea [17] and another study involved chronic pancreatitis patients [18]. Further, a study by Kotani et al [19] investigated postoperative visceral pain in patients who underwent upper or lower abdominal surgeries [18], and two studies involved healthy participants [20, 21] (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…In human studies, improvements in the pain behavioral outcomes have been consistently observed after acupuncture treatment. Acupuncture treatment showed significantly greater analgesic effects based on subjective pain ratings than sham acupuncture [16, 18, 19], and the maximum tolerable rectal sensation and distention pressure in IBS patients were significantly increased by acu-TENS compared to sham TENS [20] (Tables 2 and 5).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, spinal cord stimulation, transcranial magnetic stimulation, and acupuncture have all been proven effective in proof-of-concept studies, but rigorous evaluation in properly designed clinical trials have not yet been conducted. 29 , 43 , 44 Neurolytic procedure such as endoscopic guided plexus blocks was previously widely used for pain in CP but is now considered obsolete due to poor long-term outcomes and risk of side effects such as postural hypotension and diarrhea. 78 Thoracoscopic splanchnicectomy has been described as an alternative and minimally invasive therapy for pancreatic pain.…”
Section: Implications For Treatmentmentioning
confidence: 99%